Statistical interpretation of LDA measurements in naturally developing turbulent drag-reducing flow using invariant theory - Moataz, Mohammad; Reiter, Nina; Al-Mqbas, Mona; Metelkin, Alexander; Latifi, A.; Jovanović, J.; Delgado, Antonio (International Journal of Heat and Fluid Flow, 2022)
Turbulent drag reduction by an extremely diluted aqueous solution of polyacrylamide was studied in a fully developed plane channel flow under non-tripped flow conditions allowing the natural development of turbulence presumably from the initially laminar like a flow state. Using laser-Doppler anemometry, all components of the Reynolds stress tensor were measured. This permitted the determination of the turbulence anisotropy and independent invariants of the anisotropy tensor. Introducing a measure for the departure of the Reynolds stress tensor from the statistically axisymmetric state that ensures laminarity, fundamental insights relating the origin of turbulence and turbulent drag reduction were analyzed in light of the measured results and existing databases of direct numerical simulations. The chief mechanism relevant to the onset of turbulence and turbulent drag reduction deduced from analytic considerations involving only kinematic constraints was confirmed by the experimental data. Parametrization of the drag reduction effect in terms of the Deborah number based on turbulence quantities evaluated at the wall supports the deduction of the polymer-turbulence interaction in terms of the elastic properties of the polymer and the near-wall turbulence structure.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Turbulence measurements; Turbulence modeling; Turbulence simulation; Turbulent drag reduction